Journal of prosthodontics on dental implants - Bidra, Avinash S.; Parel, Stephen M. (Hoboken, New Jersey : Wiley Blackwell, 2015)
The Journal of Prosthodontics has been the official publication of the American College of Prosthodontics for more than 20 years. In excess of 1,000 peer-reviewed articles on a wide variety of subjects are now in print, representing a treasure chest of history and valuable information on a myriad of topics of interest to the specialty of prosthodontics.Journal of Prosthodontics on Dental Implants is a'best of' compilation of the journal's articles from a number of years, focusing exclusively on the multiple applications of osseointegrated implants: for the management of the partially edentulous patient, management of the completely edentulous patient, and management of patients with maxillofacial defects. Sections also relate to in-vitro studies and general considerations to round out the readership selections.Whether you're a subscriber who's looking for implant articles in one convenient collection or a clinician with a focus on implant dentistry looking to improve your knowledge base, Journal of Prosthodontics on Dental Implants is a must-have for your personal library.
Chapter 7: Immediate Loading of Dental Implants in the Esthetic Region Using Computer-Guided Implant Treatment Software and Stereolithographic Models for a Patient With Eating Disorders Clinical Report; Summary; Acknowledgments; References; Chapter 8: A Screwless and Cementless Technique for the Restoration of Single-Tooth Implants: A Retrospective Cohort Study ; Materials and Methods; Study Variables; Health Status Variables; Anatomic-Tooth Specific Variables; Implant-Specific Variables; Reconstructive Variables; Prosthetic-Soft Tissue Variables; Complications; Patient Questionnaire
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed August 26, 2015)
Keywords: Dental Implants -- Periodicals; Prosthodontics -- Periodicals; MEDICAL / Surgery / General; Dental implants; Prosthodontics; Periodicals; Electronic books